Implementasi Peraturan Bupati Bintan No. 1 Tahun 2019 Tentang Petunjuk Teknis Pelaksanaan Pengawasan Pendistribusian Tabung Gas 3 KG Bersubsidi Di Kecamatan Bintan Timur Kabupaten Bintan - Pardede, Jimmi Florensus; Prastya, Imam Yudhi; Winarti, Novi (Jurnal Publisitas, 2021)
The purpose of this study was to find out how the implementation of Bintan Regent Regulation No. 1 Of 2019 Concerning Technical Instructions for Supervision Of The Distribution of Subsidized 3 Kg Gas Cylinders In East Bintan District, Bintan Regency. The background of this research is due to the scarcity of 3 kg gas cylinders, so the local government issued regulations governing the distribution of subsidized 3 kg gas cylinders. However, from the data obtained, the existing data on poor families and MSMEs has a very far comparison with the number of subsidized gas cylinders circulating in the East Bintan sub-district. This study uses the theory of Van Metter and Van Horn. This research uses descriptive qualitative research method. Primary data obtained by means of interviews and observations and secondary data obtained from written reports or publications. The results of the study indicate that the implementation of the Supervision of the Distribution of Subsidized 3 Kg Gas Cylinders has not been going well. This is due to the lack of supervision and enforcement of sanctions by the local government which results in the distribution of subsidized 3 Kg gas cylinders that are not in accordance with applicable regulations.